2017
DOI: 10.1186/s12881-016-0362-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening of WT1 mutations in exon 8 and 9 in children with steroid resistant nephrotic syndrome from a single centre and establishment of a rapid screening assay using high-resolution melting analysis in a clinical setting

Abstract: BackgroundMutations in Wilm’s tumor 1 (WT1) gene is one of the commonly reported genetic mutations in children with steroid resistant nephrotic syndrome (SRNS). We report the results of direct sequencing of exons 8 and 9 of WT1 gene in 100 children with SRNS from a single centre. We standardized and validated High Resolution Melt (HRM) as a rapid and cost effective screening step to identify individuals with normal sequence and distinguish it from those with a potential mutation. Since only mutation positive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…However, reports from India including from our center showed that the prevalence of NPHS2 mutations is much lower in Indian population when compared with Europe and North American population [4% vs. 10.5–28%)] [ 7 – 12 ]. Kumar et al, reported low prevalence of WT1 mutation in south Indian population, whereas we did not detect any mutation in WT1 gene in 100 SRNS children [ 13 , 14 ]. These data suggest that a traditional genetic testing using an algorithmic approach based on age of onset of NS to prioritize the genes to be sequenced by Sanger may not be useful [ 15 , 16 ].…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, reports from India including from our center showed that the prevalence of NPHS2 mutations is much lower in Indian population when compared with Europe and North American population [4% vs. 10.5–28%)] [ 7 – 12 ]. Kumar et al, reported low prevalence of WT1 mutation in south Indian population, whereas we did not detect any mutation in WT1 gene in 100 SRNS children [ 13 , 14 ]. These data suggest that a traditional genetic testing using an algorithmic approach based on age of onset of NS to prioritize the genes to be sequenced by Sanger may not be useful [ 15 , 16 ].…”
Section: Introductioncontrasting
confidence: 82%
“…Socio demographic information, clinical and treatment details were recorded in case record forms. All these children were previously analyzed by Sanger sequencing for all the exons of NPHS2 and exon 8 and 9 of WT1 genes [ 7 , 14 ].We also included three subjects with pathogenic mutations in NPHS2 reported previously to determine the sensitivity of the targeted-NGS method [ 7 ]. Three healthy individuals were included to check sequencing efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Mutation of WT1 is commonly reported in children with steroid-resistant nephrotic syndrome, a rare disease that affect 10-15% of patients with nephrotic syndrome (12,13). About 80% of all children with sporadic nephrotic syndrome respond to steroid treatment, however, no mutations were found in WT1 in a large cohort study (14).…”
mentioning
confidence: 96%